Behavioral determinants of dental and facial esthetic self-perception among an academic population: a cross-sectional study - Ana Cristina Mafla; Mauricio Herrera-López; Juliana Estefanía Salas-Burbano; Camilo Andrés Guerrero-Dávila; Diana Paola Insuasty-Fuertes; Juan Sebastián Bustos-López; Falk Schwendicke (BMC Psychology)
Abstract Background Facial attractiveness is a relevant feature in many societies, and self-perceived attraction has been shown to affect a wide range of aspects in human lives, including quality of life. The present study assessed the mediating effects of behavioral determinants on self-reported dental and facial esthetics in an academic population. Methods A cross-sectional observational study on 1,232 students from Universidad Cooperativa de Colombia, Pasto, Colombia was conducted. Socio-demographic variables such as age, sex, residency, place of birth, living zone, socioeconomic status, and type of faculty (Dentistry, Medicine, Nursing, Engineering and Law) were included. Moreover, clinical characteristics related to oral rehabilitations of anterior teeth (composites and crowns) were recorded. Behavioral determinants such as self-esteem, self-compassion, social achievements, and social anxiety were evaluated through Rosenberg’s Self-Esteem Scale (RSE), Self-compassion Scale (SCS), Social Achievement Goal Scale (SAG) and Social Anxiety Questionnaire for Adults (SAQ-A30). The Orofacial Esthetic Scale (OES) was employed to determine self-rated dental and facial esthetics. A paper-and-pencil self-administered survey was utilized. Descriptive statistics (frequencies, means and standard deviations) were calculated to determine the levels of personal factors. Structural Equation Modeling (SEM) was performed with robust unweighted least squares estimation method to assess the mediating effects of the behavioral variables on dental and facial esthetics. Analyses were conducted using SPSS 28.0 and EQS 6.2 statistical package. Statistical significance was set at P < 0.05. Results The sample comprised 496 (40.3%) males and 736 (59.7%) females. 1,068 (86.7%) participants were 18–25 years old, and 164 (13.3%) > 25 years old. The mean and standard deviations (SD) of scales were: RSE = 24.24, SD ± 1.91; SCS = 3.16, SD ± 0.54; SAG = 32.55, SD ± 7.97; SAQ-A30 = 74.61, SD ± 21.33; and OES = 58.12, SD ± 13.12. SEM found self-compassion (β = 0.38, P = 0.03), social goals achievement (β = 0.34, P = 0.02) and self-esteem (β = 0.25, P = 0.02) had moderate and direct effects on dental and facial esthetics, while social anxiety (β = -0.19, P = 0.02) displayed a moderate indirect effect. Conclusions Behavioral factors predicted dental and facial esthetics self-perception in college students. Clinicians and educators should be aware of the identified effects which may, in turn, affect overall quality of life of patients and students.